Insights on the structure – property relationship of coconut shell lignins obtained from different microwave-assisted organosolv processes - Figueredo Sobrinho, Francisco de Assis Avelino de (2019)
Agroindustrial wastes have been extensively used as raw material for obtainment of bio-based products, such as lignin, in order to replace the petroleum-based compounds in several technological fields. Although lignin is very attractive due to its phenolic structure, its complex structure is still hinders its valorization. The aim of this work was evaluate the influence of the structural features of coconut shell lignins obtained by different microwave-assisted organosolv delignification (MWAOD) processes on their antioxidant activities. The lignin extractions were carried out using aqueous solutions of acetic or formic acid (90 % v/v and 85 % m/m, respectively) combined to an acid catalyst (Lewis or Brønsted; 2.0 % w/v or v/v) at 110 or 100 °C, respectively, during 20 minutes. Acetosolv and formosolv lignins were completely characterized through spectroscopic, chromatographic and thermal techniques. Both organosolv processes generated lignins with different yields and purities. Moreover, the utilization of acetosolv process favored the production of partial acetylated lignins, while such chemical modification was not observed when formosolv was used. The insertion of acetyl groups on acetosolv coconut shell lignins resulted in a decrease of 20 % in their glass transition temperature (Tg), yielding lignins with different processabilities. However, the higher amount of hydroxyls in formosolv lignins (approximately 20 – 30 %) favored their antioxidant capacities, presenting lower IC50 values than those of acetosolv. Nevertheless, both organosolv lignins had ten times lower IC50 values than two commercial antioxidants (BHT and Irganox 1010), which reinforces their potential on the replacement of petroleum-based derivatives. Therefore, it can be concluded that MWAOD process can be considered as a technological alternative for obtainment of lignins with high quality, different functionalities, processabilities and antioxidant capacities with potential for use in different fields of chemical and technological industries.